Pre-Competition Training for Kompetisi Sains Madrasah (KSM) at MTs Negeri 1 Pati - Sheilla Rully Anggita; Syahdatul Darainy (Community Research and Application Journal (CRAJ), 2025)
The Kompetisi Sains Madrasah (KSM) is a prestigious science competition organized by the Ministry of Religious Affairs of Indonesia to enhance student achievement in science and technology at madrasah institutions. Effective preparation through intensive coaching is essential for students to perform optimally in this competition. This community service project aimed to provide pre-competition training for KSM participants at MTs Negeri 1 Pati, preparing students and supervising teachers for the 2026 KSM. The training was conducted from October 9th – November 22nd, 2025, involving 3 students and 1 supervising teacher who participated in an intensive coaching program covering physics topics required for the KSM. The training materials included mechanics, scientific skills and scientific methods, heat and temperature, solar system, electricity and magnetism, matter and substances, light and optics, forces, energy and energy transformation, and earth and space science. The program utilized direct instruction, question-and-answer sessions, intensive problem-solving practice, simulation exercises, and final evaluations. Instructors from the Physics Department of UIN Walisongo Semarang facilitated the training, providing comprehensive coverage of physics concepts and extensive practice with KSM-style problems. Challenges encountered included limited training time and dense material coverage that reduced opportunities for extensive problem-solving practice. To address time constraints, instructors provided participants with example problems and solutions for continued independent study. The training successfully equipped participants with a deeper understanding of physics concepts relevant to KSM and improved their problem-solving skills through intensive practice. This collaboration between university faculty and madrasah demonstrates an effective model for supporting student preparation for academic competitions and enhancing the quality of science education in madrasah.